The reshaping of retail landscape in Greater Lisbon: do shopping centers have a future? - José TEIXEIRA (European Regional Science Association (ERSA), 2014)
In the early 70s, the retail landscape of the Lisbon Metropolitan Area (LMA) was mostly confined to the Lisbon downtown. However, the retail landscape is changing at a rapid pace. In the mid-80s, two focus of retail competition (Amoreiras Shopping Center and Roma Avenue) appeared out-of-city center and, in early 90s, the Cascaishopping emerged as the first large shopping center being built in the periphery of the capital. In 1998, the triad "Downtown- Amoreiras - Roma Avenue' faced the fierce competition of Colombo Shopping and Vasco da Gama Shopping and later of El Corte Inglès. On the urban periphery, the shopping centers proliferate, diversify and progress to hybrid formats. Each of these waves of change reshaped the retail landscape and changed the consumer expectations. Today, with 2.8 million inhabitants, the LMA had more than 40 shopping centers and around 4,000 stores, comprising 1.2 million m2 of GLA. The catchment areas overlap and each of the centers develops differentiation strategies to attract customers in a very competitive market, strongly affected by the economic and financial crisis that emerged in 2008 and whose epilogue still remains unclosed. The recent crisis is erasing the 'middle class' and leading to social fragmentation, which affects the retail geography of the city and requires a meticulous and creative management of shopping centers. The elites have a luxury offer in the Liberdade Avenue, while the working classes make fewer purchases and more often in fairs, street markets and Asian stores. Without a vibrant middle class, shopping centers in the LMA were strongly affected in a variety of ways: some centers become outlets; others had to close; the mix, size and location of stores changed; in all the centers there are stores closed; market rents contract; the strategies to improve the attractiveness of the centers were redesigned; and companies looked overseas markets. Our methodology includes the analysis of statistical data published by the Portuguese Council of Shopping Centers (APCC) as well as other specialized information on market developments (Cushmann & Wakefield, Jones Lang Lassalle, etc.). We then use this data to select shopping centers based on their size and type to conduct some interviews with their top managers. We suggest the differentiation as a strategy of the shopping centers to adapt to the recent changes in the retail landscape in Great Lisbon. Finally, we question the future of shopping centers and their relationship with the city and its impact on urban policies.
Keywords: 330; Retailing; Shopping Center; Consumption; Metropolitan Areas; Portugal (Lisbon); Code (R)